Kajian Filosofis Ditengah Pandemi Covid-19 Berdasarkan ParadigmaKonseling Catur Murti. - Habsy, Bakhrudin All (Universitas Nusantara PGRI Kediri, 2020)
The philosophical study of Catur Murti counseling in the midst of the COVID-19 pandemic is a deep question about problems and reality, as a reflective function and a paradigm for analytical claims of Nusantara science as a process of transformation and theoretical-ethical insight amid the problems of the COVID-19 pandemic. Catur Murti counseling paradigm restores counseling of conceptual sophistication of Nusantara's knowledge through the process of growing and developing a counseling discipline based on Nusantara culture in observing the conditions of the COVID-19 pandemic. The Catur Murti counseling, which is summarized by one of the explicit ideas in the Javanese literature tradition, namely the collection of fibers (serat-serat) of the noble teachings of Raden Mas Panji Sosrokartono, is assumed to be able to help to understand of oneself accurately, to create life perfection and to bring peace of mind in harmonizing thoughts, feelings words, and deeds in the conditions of the COVID-19 pandemic.